Implementasi Perancangan Modul Proyek P5 Oleh Guru PPKn Dalam Pembelajaran di SMP Negeri 2 Bontang - Badriyah Ayu Lestari; Hardoko Hardoko; Endang Herliah (Lembaga Pengembangan Kinerja Dosen, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a program designed by the Ministry of Education and Culture. It is important to see the readiness of educators in implementing the program because educators are the key to implementing the curriculum. The aim of this research is to reveal the readiness of educators in implementing the P5 Project Module Design by PPKn Teachers in Learning at SMP Negeri 2 Bontang. This research uses qualitative research. This research was conducted in February-March 2024. The data sources in this research used two sources, namely primary data and secondary data. Data collection techniques use observation, interviews and documentation. Analysis techniques using qualitative data techniques are data reduction, data presentation and drawing conclusions. The results of this research show that the readiness of educators in designing and implementing the Pancasila student profile project is still not optimal. This is proven by statements from educators who admitted that they still did not understand the program. This lack of understanding means that educators are unable to design P5 project modules and are less effective in implementing projects for students. The design of the P5 Project Module by the PPKn Teacher at SMP Negeri 2 Bontang resulted in the project module (P5) being a document containing the objectives, steps, media and assessments needed to implement the Strengthening Pancasila Student Profile Project.